Dilemmas of Pre-Accession Policy - Sławomir Zwierzchlewski; Katarzyna ŁASIŃSKA; Andrzej PIECZYŃSKI; Janusz SZAJNA (Communications of International Proceedings, 2023)
The functioning of the Bretton Woods System (BWS) and the European Monetary System (EMS) turned out to be a type of lesson for the architects of the European Monetary Union (EMU). In consequence, some changes were introduced to the new European system in order to make it more flexible. The nature of these changes was defined in the Maastricht Treaty (MT). These regulations were to ensure greater stability of the EMU, as the convergence of economic parameters in member states should have a positive impact on the perception of their common currency.